2019
DOI: 10.1126/sciadv.aau6696
|View full text |Cite
|
Sign up to set email alerts
|

Large spin-orbit torque efficiency enhanced by magnetic structure of collinear antiferromagnet IrMn

Abstract: Spin-orbit torque (SOT) offers promising approaches to developing energy-efficient memory devices by electric switching of magnetization. Compared to other SOT materials, metallic antiferromagnet (AFM) potentially allows the control of SOT through its magnetic structure. Here, combining the results from neutron diffraction and spin-torque ferromagnetic resonance experiments, we show that the magnetic structure of epitaxially grown L10-IrMn (a collinear AFM) is distinct from the widely presumed bulk one. It con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 49 publications
3
63
0
Order By: Relevance
“…In our previous report we found the staggered magnetic moments in L10-IrMn (001) films align with the [111] direction [22], as illustrated in Fig. 1(a).…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…In our previous report we found the staggered magnetic moments in L10-IrMn (001) films align with the [111] direction [22], as illustrated in Fig. 1(a).…”
Section: Introductionmentioning
confidence: 57%
“…The ST-FMR measurement was modulated using a sine function of low frequency. The modulated Vmix was collected using a lock-in amplifier and fitted using [4,8,22]…”
Section: B St-fmr Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a lack of clarity concerning the microscopic mechanisms of the Néel vector switching, these experiments have been widely regarded as a breakthrough in the emerging field of THz spintronics 26,30,36,[39][40][41][42][43] . It has been suggested that current-induced Néel vector dynamics in an AFM is driven primarily by the so-called Néel spin-orbit torques 29,32,[44][45][46][47][48][49][50][51][52][53][54][55][56] . The Néel spin-orbit torque originates in a non-equilibrium staggered polarization of conduction electrons on AFM sublattices 29,32,48,50 .…”
Section: Introductionmentioning
confidence: 99%